2016
DOI: 10.1017/s1368980016001191
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress during early pregnancy and birth outcomes

Abstract: Objective: Routine high-dose Fe supplementation in non-anaemic pregnant women may induce oxidative stress and eventually affect birth outcomes. The aim of the present study was to measure oxidative stress markers in pregnant women with low/normal and high Hb values in trimester 1 (Hb 1 ) and to relate these to birth weight. Design: A cross-sectional study where selected oxidative stress markers were analysed in both maternal (trimester 1; T1) and cord blood samples and correlated with birth weight. Setting: A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…Further, routine supplementation of Fe to these high Hb women for the duration of gestation resulted in persistent lower PON-1 activity in cord blood and lighter birth weights. Although these results were not measured in placental tissue, our correlations of Fe with birth weight, after covariate adjustments, is very similar to the relationship with birth weight reported by Shastri et al (2016), which may be related to over exposure to iron and subsequent increase in oxidative stress. Cadmium and lead reduce total antioxidant potential by depleting glutathione and protein-bound sulfhydryl groups that serve to neutralize free radicles (Stohs and Bagchi 1995).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Further, routine supplementation of Fe to these high Hb women for the duration of gestation resulted in persistent lower PON-1 activity in cord blood and lighter birth weights. Although these results were not measured in placental tissue, our correlations of Fe with birth weight, after covariate adjustments, is very similar to the relationship with birth weight reported by Shastri et al (2016), which may be related to over exposure to iron and subsequent increase in oxidative stress. Cadmium and lead reduce total antioxidant potential by depleting glutathione and protein-bound sulfhydryl groups that serve to neutralize free radicles (Stohs and Bagchi 1995).…”
Section: Discussionsupporting
confidence: 82%
“…The toxicity of iron-catalyzed reactive oxygen species (ROS) is well established. Shastri et al (2016) measured hemoglobin (Hb) in the first trimester of pregnancy and grouped women with high Hb levels (≥120 g/l) and compared them to women with normal to low Hb levels (< 110 g/l). Both groups continued to take an iron supplement for the duration of the pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Also, Elmas et al (25) found blood pressure and serum levels of UA, xanthine oxidase activity (XOA) and allantoin levels were higher in PE patients when compared with pregnant controls and Shastri et al (26) reported significantly higher lipid peroxides and lower paraoxonase-1 activity during 1 st trimester in pregnant women with high hemoglobin than women with low/normal hemoglobin concentration. The obtained data go in hand with Pourghassem Gargari et al (27) who detected significantly higher serum levels of MDA and significantly lower TAC in women with PE compared to controls.…”
Section: Discussion:-mentioning
confidence: 99%
“…With respect to oxidative status during pregnancy with or without any supplementation, very few studies addressed its own potential variation throughout normal gestation. The evaluation is usually carried out either early [26] or at any gestational age [9] [11] [27] [28]. Based on considerations put forth by Liochev &.…”
Section: Discussionmentioning
confidence: 99%